Continuous Traumatic Stress: Examining the Experiences and Support Needs of Women After Separation From an Abusive Partner. Issue 9 (May 2023) - Hulley, Joanne; Wager, Khai; Gomersall, Tim; Bailey, Louis; Kirkman, Gill; Gibbs, Graham; Jones, Adele D.
Intimate partner violence causes significant, long-lasting harm to almost one-third (27%) of the world's population of women. Even when women leave abusive relationships, some men continue to exercise control over their ex-partners through psychological control, threats, violence, stalking, and other forms of harassment. In this qualitative study, 52 purposively sampled women who self-identified as victims or survivors of intimate partner violence (IPV) from male partners were interviewed. Data were analyzed with a theoretically informed thematic analysis, supported by Nvivo® software. We found that leaving a violent relationship was a long-term process fraught with difficulty and ongoing risks of psychological harm. The concept of Continuous Traumatic Stress (CTS), first developed to understand the impact of state-sponsored violence and war, was found to be a particularly useful tool for the analysis of the impact of post-separation abuse. Additionally, CTS encourages researchers and practitioners to think anew about resilience-centered approaches to improving protection and access to justice for female victims.